The Influence of Electronic Word of Mouth and Price Perception on Brand Image and Repurchase Intention of Suzuki New Carry Pick Up Brand Cars in Pekanbaru City - Lestari, Milla; Samsir, S.; Wijayanto, Gatot (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
Suzuki New Carry Pick-Up had competitive sales; even though the price exceeded competitors and had several disadvantages, it had a series of advantages that attracted users with a good brand image so that repurchases occurred. This research objective is to analyze the effect of electronic word of mouth and price perceptions on brand image and the purchase intention of Suzuki New Carry PU brand cars in Pekanbaru City. The population in this study were all buyers of Suzuki New Carry PU in Pekanbaru City. Sample determination refers to Hair's criteria with the maximum likelihood estimation technique. The sample of this study was 200 people. Data will be collected using an ordinal measurement level (Likert scale) questionnaire. The data analysis technique uses partial least squares structural equation modeling with the boots-trap parameter estimation method using SmartPLS 4 software. The validity test uses the loading factor and average variance extracted, while the reliability test uses internal consistency based on the composite reliability value. The results of hypothesis testing show an effect of electronic word of mouth and price perceptions on brand image and purchase intention of Suzuki New Carry PU brand cars in Pekanbaru City.